Well logging handbook - Serra, Oberto (Éditions TECHNIP, 2008)
Annotation Contents: A. General data. B. Geology - Petrophysics. C. Processes for recording physical parameters. D. Resistivity - Conductivity logging - Electromagnetic wave propagation - Spontaneous potential. E. Magnetic susceptibility. F. Radioactivity logging: Natural radioactivity - Spectrometry of natural radioactivity. G. Density measurement - Photoelectric index measurement. H. Neutron logging: Neutron porosity measurements - Spectrometry of induced gamma rays - Chlorine logging - Termal neutron die-away measurements - Activation logging I. Nuclear magnetic resonance measurements. J. Acoustic logging: Sonic transit time measurement - Sonic amplitude and attenuation measurements - Well seismic techniques. K. Dip and borehole-wall image acquisition - Borehole caliper measurements. L. Temperature measurement. M. Rock and fluid sampling - Formation pressure measurement. Bibliography. Index
Keywords: Oil well logging -- Handbooks, manuals, etc.; elektronické knihy; electronic books